Neutrophil Lymphocyte Ratio as Screening Tool for Neonatal Sepsis in Developing Countries - Naseer, Nauman; Sheikh, Taimur Khalil; Zulfiqar, Sughra; Bashir, Huma; Haroon, Sadaf; Jahangir, Junaid (Pakistan Armed Forces Medical Journal, 2023)
Objective: to recognize an alternate method for screening neonatal sepsis in patients while considering the sensitivity and accuracy of the diagnosis. Study Design: Cross sectional study. Place and Duration of Study: Combined Military Hospital, Rawalpindi Pakistan, from Jun to Dec 2021. Methodology: Patients admitted to the Neonatal Intensive Care Unit of the Combined Military Hospital were included in the study. Demographic data, including age, weight, gender, and gestational age, were recorded. In addition, a statistical comparison of total leucocyte count, absolute neutrophil and lymphocyte counts, neutrophil-lymphocyte ratio, and C-reactive protein test was carried out for the cases and controls. Results: It was evident from the results that a significant correlation between the neutrophil-lymphocyte ratio and neonatal sepsis exists. The mean NLR in non-septic individuals was (1.8±1.3) and in septic individuals, it was (2.9±1.9). The p-value was 0.001. Furthermore, ROC showed that at an NLR value of 1.6, sensitivity was 0.594 and 1-specificity 0.295. Conclusion: Neutrophil lymphocyte ratio was an efficient screening tool for determining sepsis in neonates, with comparable results to the C-reactive protein test.